2022
DOI: 10.24042/ijsme.v5i1.11021
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of The Elementary School Teachers’ Ability to Use Technology on The Mathematics Online Learning

Abstract: In Indonesia, the implementation of online mathematics learning does not always run smoothly, there are various obstacles that occur, such as the lack of gadgets owned by teachers or students, internet networks are still weak, etc. So that the readiness of mathematics teachers in managing online learning is very necessary, especially in utilizing technology. Thus, it is necessary to analyze the readiness of mathematics teachers in carrying out online learning. In this study, we aim to describe (1) online mathe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Furthermore, in mathematical communication skills, subjects with low critical thinking skills have difficulty in visualizing the form of story questions into mathematical language, and this results in errors in drawing conclusions and even there are no calculations at all on the answer sheet. Faizah & Sugandi (2022) revealed that subjects with low communication skills have difficulty working on it so they do not do it at all. Moreover, due to low mathematical connection ability, the subject cannot explain how the procedures and concepts are related, and the relation to daily problems.…”
Section: |mentioning
confidence: 99%
“…Furthermore, in mathematical communication skills, subjects with low critical thinking skills have difficulty in visualizing the form of story questions into mathematical language, and this results in errors in drawing conclusions and even there are no calculations at all on the answer sheet. Faizah & Sugandi (2022) revealed that subjects with low communication skills have difficulty working on it so they do not do it at all. Moreover, due to low mathematical connection ability, the subject cannot explain how the procedures and concepts are related, and the relation to daily problems.…”
Section: |mentioning
confidence: 99%
“…Before designing the mentoring program, an in-depth analysis was conducted on the situations faced by teachers and students in elementary schools. Currently, many elementary school teachers still face challenges related to the use of conventional learning media in the teaching of Mathematics (Faizah & Sugandi, 2022;Panggayudi et al, 2017). Blackboards, textbooks, and traditional writing tools remain the primary choices for delivering content.…”
Section: A Introductionmentioning
confidence: 99%
“…The learning process in the experiential learning model consists of five phases, namely (1) experience phase, (2) share phase, (3) process phase, (4) generalise phase, (5) apply phase (Sari, 2018). For best results through experiential learning, students should be involved in all activities in experiential learning (Mutmainah et al, 2019;Ali, 2023). Judging from research data, it says that experiential learning can improve student learning outcomes.…”
Section: Introductionmentioning
confidence: 99%